2013
DOI: 10.1128/cmr.00002-13
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive, Model-Based Review of Vaccine and Repeat Infection Trials for Filariasis

Abstract: SUMMARY Filarial worms cause highly morbid diseases such as elephantiasis and river blindness. Since the 1940s, researchers have conducted vaccine trials in 27 different animal models of filariasis. Although no vaccine trial in a permissive model of filariasis has provided sterilizing immunity, great strides have been made toward developing vaccines that could block transmission, decrease pathological sequelae, or decrease susceptibility to infection. In this review, we have organized, to the best of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
100
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(101 citation statements)
references
References 236 publications
(397 reference statements)
0
100
1
Order By: Relevance
“…However, there are no previous vaccination experiments reported that tested the efficacy of Bm -CPI-1 or Bm -CPI-2 in this model. Many studies also implicated the potential role of antibody-mediated killing of L3 as an effector mechanism [1]. While in our present study vaccination induced a significant antigen-specific IgG antibody response against Bm -CPI-1 and Bm -CPI-2, no protection against SC L3 infection was observed.…”
Section: Discussioncontrasting
confidence: 58%
“…However, there are no previous vaccination experiments reported that tested the efficacy of Bm -CPI-1 or Bm -CPI-2 in this model. Many studies also implicated the potential role of antibody-mediated killing of L3 as an effector mechanism [1]. While in our present study vaccination induced a significant antigen-specific IgG antibody response against Bm -CPI-1 and Bm -CPI-2, no protection against SC L3 infection was observed.…”
Section: Discussioncontrasting
confidence: 58%
“…A multivalent fusion protein vaccine against B. malayi conferred 95% protection in mice (Dakshinamoorthy et al, 2013). Interestingly, it was concluded in a recent review that mice have a high degree of natural resistance to infection with B. malayi and that almost every reported vaccine trial using a wide range of vaccine components has demonstrated efficacy in mice against infection with B. malayi (Morris et al, 2013). Mice are resistant to infection with both B. malayi and O. volvulus , yet high levels of protective immunity can be induced against B. malayi , whereas only moderate levels of immunity can be induced against O. volvulus in mice regardless of the immunization regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Our analyses of ESP from L. sigmodontis vL3 reinforced our understanding of a stereotypical secretomic profile for this stage. However, no defined parasite antigens (whether alone or in combination) have reproducibly attained an equivalent level of protection to irradiated L3 in any filarial system (7). Furthermore, because a single pair of adult nematodes can generate a patent infection, vaccines directed solely against L3 face a potentially insurmountable challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Reports of possible ivermectin resistance in O. volvulus (5) and D. immitis (6) have highlighted the importance of maintaining research efforts in vaccine development against filarial nematodes. However, rational vaccine design has been constrained for several decades (7) by the intrinsic complexity of these metazoan parasites and their multistage lifecycle. Moreover, many filarial species carry obligate bacterial endosymbionts (Wolbachia), which may also stimulate the immune response during infection (8).…”
mentioning
confidence: 99%